Exploring characteristics and influencing factors of crash duration on urban arterials and collectors. Issue 9 (2nd September 2022) - Gu, Zongni; Bejleri, Ilir; Peng, Binbin
Abstract: While traffic crash duration on freeways and its association with crash characteristics have been studied extensively, limited research exists regarding the characteristics of crash duration in urban arterials and collectors and their influential factors. To better understand this relationship, this study examines the effects of crash characteristics, roadway features, temporal variables, and other variables on crash duration. To this aim, the study applies the accelerated failure time (AFT) hazards-based model on principal arterials, minor arterials, major collectors, and minor collectors using Miami-Dade County in Florida (USA) as the study area. Results show that the average crash durations in minor arterials are longer than in all other road types. When it comes to the total time duration of crashes, different types of roads have different characteristics. Specifically, when the road crashes were cleared up within 76 min, principal arterials take a shorter time than the other three types of roads to clean the scene. On the contrary, when the crash endured more than 76 min for cleanups, the crash durations in collectors were shorter than in arterials. Consistent with findings from previous studies in freeways, the results show that severe crashes are associated with increased crash durations in most urban arterials and collectors. Moreover, the impact of crash characteristics on crash duration varies across road types. A greater number of vehicles and passengers involved in crashes is associated with longer durations in all but minor collectors. With regard to roadway features, the effects on crash durations vary by road type. In addition, early morning was more likely to be associated with longer crash durations than other periods, specifically strongly affecting the crash durations in minor collectors. These findings indicate that the effects of factors on crash durations vary depending on road type and may require different actions for their effective resolution.